Analysis of infections among patients with historical culture positive for extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli or Klebsiella pneumoniae: Is ESBL-targeted therapy always needed? - Tyler J. Stone; Michael DeWitt; James W. Johnson; James R. Beardsley; Iqra Munawar; Elizabeth Palavecino; Vera P. Luther; Christopher A. Ohl; John C. Williamson (Cambridge University Press, 2023)
Abstract Objective: Among patients with a history of ESBL infection, uncertainty remains regarding whether all of these patients require ESBL-targeted therapy when presenting with a subsequent infection. We sought to determine the risks associated with a subsequent ESBL infection to help inform empiric antibiotic decisions. Methods: A retrospective cohort study of adult patients with positive index culture for Escherichia coli or Klebsiella pneumoniae (EC/KP) receiving medical care during 2017 was conducted. Risk assessments were performed to identify factors associated with subsequent infection caused by ESBL-producing EC/KP. Results: In total, 200 patients were included in the cohort, 100 with ESBL-producing EC/KP and 100 with ESBL-negative EC/KP. Of 100 patients (50%) who developed a subsequent infection, 22 infections were ESBL-producing EC/KP, 43 were other bacteria, and 35 had no or negative cultures. Subsequent infection caused by ESBL-producing EC/KP only occurred when the index culture was also ESBL-producing (22 vs 0). Among those with ESBL-producing index culture, the incidences of subsequent infection caused by ESBL-producing EC/KP versus other bacterial subsequent infection were similar (22 vs 18; P = .428). Factors associated with subsequent infection caused by ESBL-producing EC/KP include history of ESBL-producing index culture, time ≤180 days between index culture and subsequent infection, male sex, and Charlson comorbidity index score >3. Conclusions: History of ESBL-producing EC/KP culture is associated with subsequent infection caused by ESBL-producing EC/KP, particularly within 180 days after the historical culture. Among patients presenting with infection and a history of ESBL-producing EC/KP, other factors should be considered in making empiric antibiotic decisions, and ESBL-targeted therapy may not always be warranted.